Pain relief and palliative care program for advanced cancer, Llay-Llay, January 2001-February 2004 - Ebner, Paula; Cuevas, Claudia; Swett, Eduardo; Yentzen, Gladys (Revista Chilena de Salud Pública, 2005)
Cancer is a reality present in the Chilean popularion, a fact which compels the public health system to implement programs dealing with the different clinical stages of cancer, among them,the National Program for Pain Relief in Cancer and its Palliative Care. The aim of this study is that of evaluating the development of this program in a type IV hospital, and establishing whether the objectives propounded by the Ministry of Health are being observed. This is a descriptive study of 72 patients incorporated into the program, analyzing variables such as time of permanence, decrease of pain and analgesic treatment. A 38.9% of the patients were aware of their pathology upon entry. The majority (73.6%) remained in the program for as long as 3 months. Upon entry to the program, 62% had a visual-analogue scale (VAS) equal to 4 or higher. Upon departure, on the other hand, 95.7% had a VAS below 4. A 9.7% entered the program without analgesic treatment, 23.6% with treatment based on non-steroidal antiinflammatory drugs (NSAIDs) and 66.7% using some opiate. The deceased 1.4% received no analgesic treatment. As far as services delivered, there were 4.7 office visits per month. As far as outpatient visits are concerned, 1.47 visits took place per month. An average of 1.35 workshops per person were carried out. This program, which was started in 1997, provides adequate benefits to cover the main objective contemplated, which is that of diminishing pain to the incorporated patients, thus improving their quality of life to reach a worthy and peaceful death.